Content and language integrated learning : evidence from research in Europe - Ruiz de Zarobe, Yolanda; Jiménez Catalán, Rosa Ma. (Rosa María) (Second language acquisition (Clevedon, England), 2009)
Contributes to the growth of interest in Content and Language Integrated Learning (CLIL), an approach to second/foreign language learning that requires the use of the target language to learn content. This book brings together the analyses on theoretical and implementation issues of CLIL.